2018
DOI: 10.18805/lr-423
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genetic diversity and population structure of Turkish common bean germplasm by the iPBS-retrotransposons markers

Abstract: Present study was aimed to investigate the genetic diversity and population structure of Turkish common bean germplasm. A total of 96 bean genotypes were characterized with iPBS-retrotansposons that yielded a mean polymorphism information contents of 0.8. Mean gene diversity and Shannon information index were 0.14 and 0.25, respectively. Neighbor joining analysis divided the bean genotypes into two main group (A and B) according to their geographical regions, growth habits and seed size. Bingol-l7, Sivas-14 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
2
13
2
Order By: Relevance
“…Mean polymorphism obtained in this study was 83.98%, which varied from 72.72% to 100%. Mean polymorphism obtained in this study was found greater than reported by Sevindik [47] for laurel, Yaldiz et al [25] for tobacco and Aydin and Baloch [48] using iPBS-retrotransposons and thus confirming greater variations in Turkish laurel germplasm. The PIC value is used to understand the efficiency of polymorphic loci for the identification of genetic diversity [43] and explore the discriminating power marker among genotypes [40].…”
Section: Polymorphism In Turkish Laurel Germplasm Revealed By Ipb-retsupporting
confidence: 77%
See 2 more Smart Citations
“…Mean polymorphism obtained in this study was 83.98%, which varied from 72.72% to 100%. Mean polymorphism obtained in this study was found greater than reported by Sevindik [47] for laurel, Yaldiz et al [25] for tobacco and Aydin and Baloch [48] using iPBS-retrotransposons and thus confirming greater variations in Turkish laurel germplasm. The PIC value is used to understand the efficiency of polymorphic loci for the identification of genetic diversity [43] and explore the discriminating power marker among genotypes [40].…”
Section: Polymorphism In Turkish Laurel Germplasm Revealed By Ipb-retsupporting
confidence: 77%
“…Mean effective number of alleles (1.36) found in this study were higher than the reported by previous studies in various crops using iPBS-retrotransposons markers [25,50]. Mean gene diversity (0.22) resulted in this study was found higher than the reported by earlier studies [25,48,50] and thus explains the presence of higher diversity in studied germplasm. Shannon's information index is an important criterion to understand the variation as it distinguishes the genetic diversity in a population combining abundance and evenness [51].…”
Section: Genetic Diversity and Population Evaluation For Turkish Laurcontrasting
confidence: 73%
See 1 more Smart Citation
“…Earlier studies have confirmed the clustering of common bean germplasm based on plant height, 100-seed weight, and collection point. These previous reports strengthen the findings of our study [63].…”
Section: Dartseq Markers Analysis and Ldsupporting
confidence: 93%
“…Turkey is not a center of origin of common bean and it is supposed that it was introduced to Turkey from Europe in the 17th century by the Ottoman traders travelling between Europe and Asia [9][10][11]. Bean landraces present in small farmers' fields are playing a vital role in the country's economy [12,13]. Annual common bean production of Turkey was 235,000 tons versus nearly 26,833,394 tons of common bean produced worldwide [14].…”
Section: Introductionmentioning
confidence: 99%